Tradisionalisme Pesantren di Tengah Arus Perubahan - Mukodi Mukodi (Jurnal Penelitian Pendidikan, 2013)
Various problems arise and sunk in traditional boarding school, as if thoseadapted space and time. Study object of boarding school is always exciting to berevealed, because it always lives to grow and to metamorphose with the spirit ofthe time. The focus of this study is boarding school traditionalism, especially inthe practice of traditional boarding school life among the current change. Thisstudy aims to unravel the current traditionalism landscape of boarding schooleducation, as well as answer the various problems highlighting traditionalboarding school cubicles. Students’ receiving systems, learning systems, andmanagement systems that are "completely traditional” to be the identity oftraditional boarding school itself (salafiyah). There are four alternative solutionsin order that the boarding school traditionalism even survives in the global era,namely to: 1) focus on specific skills, 2) develop entrepreneur; 3) graft schoolinginstitution; 4) institutionalize its boarding school.